2012
DOI: 10.1002/ptr.4899
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular Protection and Antioxidant Activity of the Extracts from the Mycelia of Cordyceps Sinensis Act Partially Via Adenosine Receptors

Abstract: Mycelia of cultured Cordyceps sinensis (CS) is one of the most common substitutes for natural CS and was approved for arrhythmia in China. However, the role of CS in ameliorating injury during ischemia-reperfusion (I/R) is still unclear. We examined effects of extracts from CS on I/R and investigated the possible mechanisms. Post-ischemic coronary perfusion pressure, ventricular function, and coronary flow were measured using the Langendorff mouse heart model. Oxidative stress of cardiac homogenates was perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 42 publications
(46 reference statements)
0
21
0
Order By: Relevance
“…As one of the end-products in the lipid peroxidation process, MDA has been used to evaluate the severity of oxygen-derived free radical-mediated injuries [18]. On the other hand, the body has an endogenous antioxidant system, which is composed of various antioxidant enzymes, to defend against the potential deleterious consequences of ROS and to protect against various forms of peroxidative injuries [19]. It is commonly accepted that SOD and GSH-Px are two dominant anti-oxidative enzymes.…”
Section: Discussionmentioning
confidence: 99%
“…As one of the end-products in the lipid peroxidation process, MDA has been used to evaluate the severity of oxygen-derived free radical-mediated injuries [18]. On the other hand, the body has an endogenous antioxidant system, which is composed of various antioxidant enzymes, to defend against the potential deleterious consequences of ROS and to protect against various forms of peroxidative injuries [19]. It is commonly accepted that SOD and GSH-Px are two dominant anti-oxidative enzymes.…”
Section: Discussionmentioning
confidence: 99%
“…Further study has shown that Cordyceps sinensis affords cardioprotection by reduced postischemic diastolic dysfunction and improved recovery of pressure development and coronary flow. Moreover, this study has also suggested that preischemic adenosine receptor activation may be involved in reducing contracture in hearts pretreated with Cordyceps sinensis [99]. …”
Section: Herbal and Traditional Medicines And Cardiorenal Syndromementioning
confidence: 99%
“…As we reported previously, the renoprotective efficacy of C sinensis was confirmed by its ameliorating metabolic abnor-www.nature.com/aps Liu X et al Acta Pharmacologica Sinica npg malities in the kidneys of rats with CKD [9] . Additionally, C sinensis has also been identified to play significant roles in the protection of liver [10] and heart [11,12] tissue from pathological impairments; thus, we hypothesized that C sinensis could also improve the metabolic function of the extrarenal organs, such as the heart and liver, to achieve its therapeutic effects on the kidney.…”
Section: Introductionmentioning
confidence: 99%